2023
DOI: 10.3390/molecules28207218
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and In Vitro Biological Assay of Thermo-Mechanically Tuned Chitosan Reinforced Polyurethane Composites

Nadia Akram,
Iram Shahzadi,
Khalid Mahmood Zia
et al.

Abstract: The progressive trend of utilizing bioactive materials constitutes diverse materials exhibiting biocompatibility. The innovative aspect of this research is the tuning of the thermo-mechanical behavior of polyurethane (PU) composites with improved biocompatibility for vibrant applications. Polycaprolactone (CAPA) Mn = 2000 g-mol−1 was used as a macrodiol, along with toluene diisocyanate (TDI) and hexamethylene diisocyanate (HMDI), to develop prepolymer chains, which were terminated with 1,4 butane diol (BD). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Kara et al added silver ions onto the surface of PU-chitosan films and the antibacterial rates were 27% and 54% [32]. Akram et al prepared chitosan/PU composites and the antibacterial rates were 45% and 42% [33]. Drozd et al prepared PU coated with chitosan/heparin and the antibacterial rates were 53% and 51%, respectively [16].…”
Section: Analysis Of Antibacterial Resultsmentioning
confidence: 99%
“…Kara et al added silver ions onto the surface of PU-chitosan films and the antibacterial rates were 27% and 54% [32]. Akram et al prepared chitosan/PU composites and the antibacterial rates were 45% and 42% [33]. Drozd et al prepared PU coated with chitosan/heparin and the antibacterial rates were 53% and 51%, respectively [16].…”
Section: Analysis Of Antibacterial Resultsmentioning
confidence: 99%
“… 30 Akram et al have reported on the fabrication of chitosan-reinforced polyurethanes. 31 Marta and coworkers have reported on the properties, modification and applications of banana starch. 32 Jana and coworkers have provided details about the wheat starch structure–function relationship in bread making.…”
Section: Introductionmentioning
confidence: 99%